Hydroamination/hydrosilylation sequence catalyzed by titanium complexes - Heutling, Andreas; Doye, Sven (Angewandte Chemie. International edition, 2005)
A single precatalyst is used for the sequential combination of the Ti-catalyzed hydroamination of alkynes with the Ti-catalyzed hydrosilylation of imines. In this way alkynes and primary amines are converted efficiently into secondary amines in a fully catalytic one-pot process (see scheme).
Gesehen am 26.03.2018